2017
DOI: 10.1177/0300060517723252
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of respiratory muscle strength, pulmonary function, and functional capacity with quality of life in patients with atrial fibrillation

Abstract: ObjectiveTo examine the relationship of pulmonary parameters and functional capacity with quality of life (QoL) in patients with atrial fibrillation (AF).MethodsThirty-six patients with chronic AF were included in this cross-sectional study. QoL was assessed with the Medical Outcomes Survey 36-item Short Form (SF-36) and Minnesota Living with Heart Failure Questionnaire (MLHFQ). Respiratory muscle strength and pulmonary function were also measured. Functional capacity was assessed with the 6-min walk test (6MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…On the other hand, significance values further suggest that expiratory muscle strength may be more correlated with functional capacity than inspiratory muscle strength. Our results are in agreement with previous studies reporting the potential relationship between inspiratory muscle strength and functional capacity (Demir et al, 2018;Zeren et al, 2016). Furthermore, it has been reported that respiratory muscle weakness is associated with reduced functional capacity in hemodialysis patients (Figueiredo et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, significance values further suggest that expiratory muscle strength may be more correlated with functional capacity than inspiratory muscle strength. Our results are in agreement with previous studies reporting the potential relationship between inspiratory muscle strength and functional capacity (Demir et al, 2018;Zeren et al, 2016). Furthermore, it has been reported that respiratory muscle weakness is associated with reduced functional capacity in hemodialysis patients (Figueiredo et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, IMS values were negatively correlated with anxiety and depression in preoperative heart surgery. Similarly, Demir et al 35 reported that IMS and FC are negatively associated with quality of life (e.g., emotional dimension) among patients with atrial fibrillation. Therefore, a poor IMS and low FC are associated with poor psychological health conditions, and also cardiorespiratory fitness is one of the predictors of mortality in patients with OHS.…”
Section: Discussionmentioning
confidence: 91%
“…Anxiety and depression might affect the severity of a patient's symptoms, leading to a poorer quality of life for the patients. 35,36 One explanation might be that these patients required cardiac surgery because they either had intractable angina from CAD or extreme dyspnea from valvular disease. It is possible that the more severe their disease, the worse their preoperative symptoms were, and the less they were able to perform daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of recent improvements in science and technology, as well as more successful cardiovascular disease diagnosis, the number of people living with congenital heart disorders (CHD) and reaching adulthood is increasing [ 1 , 2 ]. Congenital heart disease (CHD) patients have a variety of physiologic issues, including decreased aerobic capacity, exertional dyspnea, cardiovascular and peripheral muscle deconditioning, and muscle atrophy and weakness [ 3 , 4 , 5 ]. There is earlier evidence that exercise capacity is not regulated by cardiac variables in isolation, but depends on a complex interplay between cardiopulmonary and muscular components in CHD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%